THE IMPACT OF HUMAN ACTIVITIES ON ENVIRONMENTAL SUSTAINABILITY - Mohammed Jabar Odah Inbit; Mohamed abdulhassan eliwi alkolany; Ahmed Abd Ali Kazem; Hussain Hamza Hussein; Raed Abd AL-kadum mageed Brism (Journal of Medical Genetics and Clinical Biology, 2024)
-